2019
DOI: 10.1080/23311932.2019.1567042
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Hyacinth Invasion on Smallholder Farming along River Tano and Tano Lagoon, Ghana

Abstract: Water hyacinth invasion and its associated effects have been reported to be a source of problems to riparian people, posing challenges to activities like fishing and farming along invaded waterbodies. Based on cross-sectional research with 55 farmers who were sampled using the snowballing sampling technique, this study assesses the effects of water hyacinth invasion on smallholder farming activities in the Jomoro District. Four communities along the River Tano and Tano Lagoon in the district were purposively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
12
1
4
Order By: Relevance
“…De Groote et al (2003) reported that close of 1/3 rd of the respondents was affected by the itching. An increasing the prevalence rate of malaria and bilharziosis that were reported in previous studies [28,33] were not observed by the respondents and participants of FGDs after the weed infested Lake Tana. However, the research done by [38] in the same study area revealed that the physical abstraction of water hyacinth provided a very good habitat for the proliferation of mosquito larvae.…”
Section: Plos Onecontrasting
confidence: 47%
See 2 more Smart Citations
“…De Groote et al (2003) reported that close of 1/3 rd of the respondents was affected by the itching. An increasing the prevalence rate of malaria and bilharziosis that were reported in previous studies [28,33] were not observed by the respondents and participants of FGDs after the weed infested Lake Tana. However, the research done by [38] in the same study area revealed that the physical abstraction of water hyacinth provided a very good habitat for the proliferation of mosquito larvae.…”
Section: Plos Onecontrasting
confidence: 47%
“…The effect of water hyacinth on the farming activities was also observed along River Tano and Tano Lagoon, Ghana [28]. The influence of the weed on farm activities of smallholder farmers however was not creating the work burden by increasing labor demand like Lake Tana area.…”
Section: Plos Onementioning
confidence: 88%
See 1 more Smart Citation
“…Los cuerpos de agua en estos contextos son focos de desarrollo económico, convirtiéndose en los cimientos de la economía de la zona (Güereña et al, 2015;Honlah et al, 2019;Waithaka et al, 2017). Alrededor de ellos se desarrollan actividades económicas como la pesca, la agricultura, infraestructuras de generación de energía o actividades recreativas vinculada al turismo, entre otros (Téllez et al, 2008;Villamagna and Murphy, 2010;Waithaka et al, 2017).…”
Section: Impactos Provocados Por La Plagaunclassified
“…La densa red que genera el JA impide la salida del puerto de las embarcaciones de menor calado, dificultando la actividad pesquera. Este tipo de embarcaciones son las más perjudicadas ya que invierten mucho tiempo en el transporte, lo que se traduce en un aumento del gasto en gasolina y, por lo tanto, una reducción en los beneficios de su actividad productiva (Güereña et al, 2015;Honlah et al, 2019;Mbula, 2016). Según los datos reportados del trabajo de campo realizado por Oladimeji et al a lo largo del río Níger a su paso por Nigeria (Oladimeji et al, 2016), la infección de JA provocó una pérdida del 20 % de la actividad productiva pesquera.…”
Section: Impactos Provocados Por La Plagaunclassified